Business leaders' views on the importance of strategic and dynamic capabilities for successful financial and non-financial business performance. Issue 7 (14th September 2015) - Simon, Alan; Bartle, Chloe; Stockport, Gary; Smith, Brett; Klobas, Jane E.; Sohal, Amrik
Abstract : Purpose: – The purpose of this paper is to report on research that identifies the relationships that senior managers believe exist between capabilities and business success. In doing so, it addresses the need for more empirical research about the role of strategic and dynamic capabilities in organisational performance. It also highlights the critical strategic and dynamic capabilities that are most valuable for practising managers. Design/methodology/approach: – A multi-method study was conducted. Eight types of strategic capability and ten types of dynamic capability commonly found in organisations were identified through consecutive literature review, web site content analysis and interviews with senior executives. A questionnaire survey was then used to ask senior officers of publicly listed Australian firms about the importance of each capability and financial and non-financial performance indicators. The relationship between capabilities and performance was measured by regression modelling. Findings: – Good leadership with an innovative vision and selection and retention of good staff and developing their skills and capabilities were the stand out strategic capabilities. Strategic thinking about the big picture and the long-term and flexible leaders who can lead and manage adaptation to change were considered to be the most important dynamic capabilities. Strategic capabilities were more often associated with indicators of financial success, and dynamic capabilities were more often associated with non-financial measures of organisational performance. Originality/value: – This is the first study to make a distinction between strategic and dynamic capabilities in examining the relationship between capabilities and business success. The results demonstrate that the distinction has both theoretical and practical value.